Impactos sociais da atividade turística: um estudo de caso em Tibau do Sul/RN - Grande, Mariana Benetti de (2009)
This study has been presented for the Master in business of the Universidade Federal do Rio Grande do Norte, the objectives are evaluate the social impacts of the tourism in the community of Tibau do Sul in the state of Rio Grande do Norte. The research is a study of case and the analysis is qualitative and quantitative. The tourism is considerate for many people as an important source of richness, job and an important economic activity. However, for being an activity that involves as main element people, It can cause impacts, could these are beneficial or malign. To evaluate the community's perception about these impacts, it was applied a questionnaire returned to the perceptions of them about the next social indicators: health, job, security, education and life quality. Considering the advent of the tourist activity in a period fifteen year. Through the research could conclude that, of general form the population realizes the changes occurred in the municipal district of positive way. Except for some indicators that receive negative evaluation